Avaliação do vigor de sementes crioulas de milho (zea mays l.) utilizando testes tradicionais e análise de imagens - Silva, Kelem Cristiany Nunes (2020)
Heirloom seeds are varieties adapted or produced usually by family farmers, considered a basic resource of great importance for autonomy as well as food and nutritional security, necessary for the permanence of farmers in the field. Seed quality evaluation through vigor tests represents an important aid for these farmers, with the aim of classifying these materials into different levels of vigor. Thus, the objective was to evaluate the efficiency of physical, physiological and sanitary tests in the classification of lots of heirloom seeds of maize (Zea mays L.), compared to a commercial cultivar, as well as comparing the results of the image analysis of seedlings grown from these seeds with those obtained by traditional physiological analyses. Twenty-four lots of heirloom maize purchased in seven regions of western Rio Grande do Norte and a commercial cultivar distributed by the Seed Bank Program of Rio Grande do Norte State were evaluated. The physical quality was determined by the following tests: moisture content, physical purity, determination of other seeds and 1000-seed weight. For sanitary quality, infested seeds were examined. Physiological quality was determined by germination test, first count, shoot and root length, shoot and root dry mass, emergence, emergence speed index, accelerated aging, electrical conductivity and potassium leakage. The System for Seedling Analysis (Sistema de Análise de Plântulas - SAPL) was used to calculate seedling length, uniformity, growth and vigor indices. Physical and physiological tests are efficient in classifying lots into different levels of vigor, but SAPL does not stratify lots as traditional tests do. The commercial cultivar used in the present study showed lower physiological potential than heirloom seeds in most of the tests performed.